Communication Processes for Peace - Toro Calonje, Alejandra (Anagramas Rumbos y Sentidos de la ComunicaciÃ³n, 2020)
The reflection presented here emanates from two investigations carried out with women victims of political violence in Colombia, both located in the field of Social Communication. Methodologically, hypothesis of imperfect peace theory and peace research were tested based on artistic transcoding exercises through processes conceived from a Social Communication perception and performed by victims of the conflict. Its purpose was to produce a personal artistic work from pre-existing ones. Taking as a starting point the stories of their experiences, participants confronted artistic pieces and transformed thesa work that inspired them, to create another one of their own. This experience, according to these theories, fosters the mourning and resilience of victims through personal empowerment, fundamental to peace. The social background of these experiences has been the post-conflict following the peace agreements between the farc and the government. The first process was advanced with Afro-descendant women displaced from the Pacific to Cali; the second with students socially disadvantaged by violence in their home regions. These exercises resulted in a change in womenâ€™s perception of their violent personal experience and, as a consequence, in their ability to make peace.